A lithotrophic microbial fuel cell operated with pseudomonads-dominated iron-oxidizing bacteria enriched at the anode - Thuy Thu Nguyen; Tha Thanh Thi Luong; Phuong Hoang Nguyen Tran; Ha Thi Viet Bui; Huy Quang Nguyen; Hang Thuy Dinh; KIM, BYUNG HONG; Hai The Pham (WILEY, 2015)
In this study, we attempted to enrich neutrophilic iron bacteria in a microbial fuel cell (MFC)-type reactor in order to develop a lithotrophic MFC system that can utilize ferrous iron as an inorganic electron donor and operate at neutral pHs. Electrical currents were steadily generated at an average level of 0.6mA (or 0.024mA cm(-2) of membrane area) in reactors initially inoculated with microbial sources and operated with 20mM Fe2+ as the sole electron donor and 10ohm external resistance; whereas in an uninoculated reactor (the control), the average current level only reached 0.2mA (or 0.008mAcm(-2) of membrane area). In an inoculated MFC, the generation of electrical currents was correlated with increases in cell density of bacteria in the anode suspension and coupled with the oxidation of ferrous iron. Cultivation-based and denaturing gradient gel electrophoresis analyses both show the dominance of some Pseudomonas species in the anode communities of the MFCs. Fluorescent in-situ hybridization results revealed significant increases of neutrophilic iron-oxidizing bacteria in the anode community of an inoculated MFC. The results, altogether, prove the successful development of a lithotrophic MFC system with iron bacteria enriched at its anode and suggest a chemolithotrophic anode reaction involving some Pseudomonas species as key players in such a system. The system potentially offers unique applications, such as accelerated bioremediation or on-site biodetection of iron and/or manganese in water samples.